The Autonomous Thinking Teacher: Preparing English Teachers for the 21st Century - Alexius Chia; Stefanie Chye; Bee-Leng Chua (The English Teacher, 2021)
This concept paper describes the changes made to Singapore’s initial teacher preparation (ITP) programmes with a specific focus on its thinking teacher model (NIE, 2009) – a model of teacher agency and an approach to ITP that requires self-reflection on roles and practice, understanding theories and research, and adapting to changing learner needs (Tan & Liu, 2015). An important component of this model is a ‘meta’ course which all pre-service teachers are required to undergo. This ‘meta’ course called Professional Practice and Inquiry (PPI) initiative – which was introduced to develop reflective professionals – cuts through the entire ITP programme providing them with both a framework and a platform to curate their understandings across all their courses, reflect deeply about teaching and learning and highlight their best work. This paper demonstrates, by the use of vignettes from their reflective pieces, how the goals and various components made possible by the PPI initiative provided the impetus for English pre-service teachers to develop into autonomous thinking teachers.